STUDY OF FOOTWAY AND BIKE TRAVEL FACILITIES AS A PUBLIC TRANSPORT MODE INTEGRATION FACILITY IN SOUTH TANGERANG CITY (CASE STUDY: SUDIMARA STATION) - Sah, Muhammad Baharudin (ASTONJADRO, 2021)
It is known that South Tangerang City is one of the fastest growing cities. This indicates that the increasing number of users of transportation means that facilities for transportation users need to be considered, one example is pedestrians. The unrealized development of pedestrian facilities is caused by the transfer of function of pedestrian facilities for public needs and insufficient space for pedestrians. The lack of pedestrian facilities causes pedestrians to pass by and has an impact on public transportation that is currently operating, causing congestion. Sudimara Station is located in Ciputat District, South Tanggerang City, with a population growth rate of 3.0% in 2019. All buildings are provided for pedestrians to provide services to pedestrians so as to improve pedestrian smoothness, safety and comfort. The purpose of this study was to analyze the performance of pedestrian facilities at Sudimara Station. The method used is direct field survey and data processing using Microsoft Excel, AutoCad. The results of the author's research include the minimum width of the sidewalk in 2020 and 2025 of 1.5 - 1.6 meters and the service level of pedestrian facilities is classified as A, which means that pedestrians can walk freely, including being able to determine the direction of walking freely, at speed. relatively fast without causing interference between pedestrians. the existing conditions of the sidewalks in 2020, namely there are several obstacles for pedestrians such as the presence of street vendors, public transportation parking carelessly, and several motorbikes parked carelessly, buying and selling activities in markets close to Sudimara station and the absence of integration facilities around the place. the. Planning that the authors do is to increase the width of the sidewalk to 1.5 meters, and the addition of street lighting facilities.